SEMAI: Nine Anti-Corruption Values in Traditional Games as a Promotive Form in Early Children - Fajarrini, Arsyia (JOYCED: Journal of Early Childhood Education, 2024)
Nowadays, many children do not know traditional games, especially in urban areas. This is because the development of increasingly sophisticated technology makes children more interested in playing gadgets than playing with their friends. Aim this research is to find out the anti-corruption values contained in traditional games. This research method is a literature study, researchers explore or examine books, journals or other data that are in accordance with the research theme. The steps in this research are topic selection, information exploration, determining the focus of research, collecting data sources, presenting data and compiling research results. The analysis technique in this research uses the content analysis method. Researchers selected, compared, combined and categorized the research results according to the research theme. The result of this research is that every traditional game in Indonesia has positive character values that can shape children's character. The character values contained in these traditional games are in accordance with the nine anti-corruption values set by the KPK. These values include honesty, justice, discipline, independence, responsibility, caring, courage, hard work and simplicity